The Synthetic Peptide LyeTx I mn∆K, Derived from Lycosa erythrognatha Spider Toxin, Is Active against Methicillin-Resistant Staphylococcus aureus (MRSA) In Vitro and In Vivo - Ana Paula Gonçalves Coelho Vieira; Amanda Neves de Souza; William Gustavo Lima; Julio Cesar Moreira Brito; Daniela Carolina Simião; Lucas Vinícius Ribeiro Gonçalves; Lídia Pereira Barbosa Cordeiro; Denise de Oliveira Scoaris; Simone Odília Antunes Fernandes; Jarbas Magalhães Resende; Burkhard Bechinger; Rodrigo Moreira Verly; et al. (MDPI AG, 2024)
The urgent global health challenge posed by methicillin-resistant Staphylococcus aureus (MRSA) infections demands effective solutions. Antimicrobial peptides (AMPs) represent promising tools of research of new antibacterial agents and LyeTx I mn∆K, a short synthetic peptide based on the Lycosa erythrognatha spider venom, is a good representative. This study focused on analyzing the antimicrobial activities of LyeTx I mn∆K, including minimum inhibitory and bactericidal concentrations, synergy and resensitization assays, lysis activity, the effect on biofilm, and the bacterial death curve in MRSA. Additionally, its characterization was conducted through isothermal titration calorimetry, dynamic light scattering, calcein release, and finally, efficacy in a mice wound model. The peptide demonstrates remarkable efficacy against planktonic cells (MIC 8-16 µM) and biofilms (>30% of inhibition) of MRSA, and outperforms vancomycin in terms of rapid bactericidal action and anti-biofilm effects. The mechanism involves significant membrane damage. Interactions with bacterial model membranes, including those with lysylphosphatidylglycerol (LysylPOPG) modifications, highlight the versatility and selectivity of this compound. Also, the peptide has the ability to sensitize resistant bacteria to conventional antibiotics, showing potential for combinatory therapy. Furthermore, using an in vivo model, this study showed that a formulated gel containing the peptide proved superior to vancomycin in treating MRSA-induced wounds in mice. Together, the results highlight LyeTx I mnΔK as a promising prototype for the development of effective therapeutic strategies against superficial MRSA infections.